TRANSMISSION DYNAMICS AND CONTROL STRATEGIES FOR BACTERIAL ZOONOTIC DISEASES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Bacterial zoonoses represent critical public health challenges at the human-animal-environment interface, with transmission mechanisms varying by pathogen ecology and host behavior. This analysis examines the epidemiological pathways through which bacterial pathogens traverse species boundaries, evaluating reservoir dynamics, environmental persistence, and anthropogenic risk factors. Evidence demonstrates that integrated surveillance systems combining veterinary monitoring with environmental sampling significantly reduce disease burden. The strategic application of biosecurity protocols, targeted vaccination programs, and risk-based interventions in high-exposure populations offers measurable protection. Understanding transmission mechanisms remains fundamental to developing effective control frameworks that address both endemic persistence and emerging outbreak scenarios.